2001
DOI: 10.1002/j.2161-1920.2001.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Career development of trauma survivors: expectations about counseling and career maturity

Abstract: Trauma survivors are individuals who have been involved in an experience that includes the likelihood of loss of life or grievous harm to oneself or others (Allen, 1995;Matsakis, 1998; Rosenbloom, Williams, & Watkins, 1999). Trauma survivors may have experienced an accident, natural disaster, abuse, crime victimization, or violence including sexual assault, incest, or physical abuse (Rosenbloom et al., 1999). Shengold (1979) referred to trauma events as indignities imposed by one human being upon another and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…In addition, significant and meaningful differences were found between the low-and-high trauma groups for all the career variables used in this study. Upon reanalysis, these results are similar to those of Coursol et al (2001), who found small to medium effect sizes for the CMI Total score, the CMI Involvement subscale, and the CMI Independence subscale. The results of the correlation between trauma symptoms and career thoughts indicate that as trauma symptoms increase so does the level of dysfunctional career thoughts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, significant and meaningful differences were found between the low-and-high trauma groups for all the career variables used in this study. Upon reanalysis, these results are similar to those of Coursol et al (2001), who found small to medium effect sizes for the CMI Total score, the CMI Involvement subscale, and the CMI Independence subscale. The results of the correlation between trauma symptoms and career thoughts indicate that as trauma symptoms increase so does the level of dysfunctional career thoughts.…”
Section: Discussionsupporting
confidence: 90%
“…Peterson & Prior, 2000;Rosenbloom et al, 1999). Coursol et al (2001) suggested that one aspect of an individual's functioning that may be affected by exposure to traumatic events is the ability of the individual to engage in the career-and work-related activities needed to reach his or her full potential within the world of work. To date, there has been limited research and discussion regarding the relationship between trauma symptoms, career development, and vocational behavior.…”
mentioning
confidence: 99%
“…Research on expectations in counseling has been conducted, ranging from different client characteristics expectations, expectations of content to more behavioural expectations (e.g. Coursol, Lewis, & Garrity, 2001;Galasi et al, 1992;Tinsley Tokar & Helwig, 1994;Tracy & Dundon, 1988). The primary focus in these investigations has been on the clients' expectation and perception.…”
mentioning
confidence: 98%
“…Impaired functioning across multiple domains (e.g., interpersonal, developmental, physical) is a necessary diagnostic criterion associated with posttraumatic stress disorder (PTSD), including impaired functioning in occupational domains (American Psychiatric Association, 2013). In addition, those who have experienced trauma or are living with PTSD may have overall issues with career maturity or issues in the workplace, such as difficulty communicating with coworkers and completing job responsibilities promptly (Coursol, Lewis, & Garrity, 2001; Wald, 2009). Female survivors of interpersonal violence have experienced challenges returning to work following their trauma, including physical health concerns, social isolation, feeling disconnected, and a loss of control (Ballou, Balogun, Gittens, Matsumoto, & Sanchez, 2015).…”
Section: Trauma and Career Developmentmentioning
confidence: 99%